Employee Well-being and Organisational Performance: a Serious Game for Investigating Perceived Social Impacts of Digital Technologies - Nemoto, Y.; Kobelt, Dennis; Herrmann, Jan-Phillip; Tackenberg, Sven (ARBEIT HUMAINE gestalten : 67. Kongress der Gesellschaft für Arbeitswissenschaft e. V.)
The rapid spread of digital technologies is changing work systems and how people do their work. The positive and negative impacts of these technologies have heatedly discussed by researchers and practitioners. However, there is little research on how people perceive the impacts of digital technologies from both individual and organisational perspectives. To contribute to this issue, the present study aims to develop a serious game for collecting data about players’ perceptions and decisions in virtual organisational activities. The characteristics of the developed game are that players select their criteria for impact assessment and that they solve organisational problems by traditional or technological solutions. This paper proposes the game rules and processes and demonstrates an analysis of collected data.